Injuries and their probable causes in undergraduates of the Physical Education course at the State University of Maringá - Alberto Saturno Madureira; Simone Borges Machado (Revista da Educação Física)
The aim of this study to analyse the occurrence of injuries in undergraduates of the Physical Education Course at the State University of Maringá. Types of injuries were diagnosed, the opinion of students and professors with regard to their probable causes was taken and the factors that could render injuries less damaging were identified. Research was carried out in the second semester of 1991 when 231 students were regularly enlisted. Data were collected by means of questionnaires for professors and for students. Forty injury cases were verified, 13 with males and 27 with females. The most common type of injury was bruises (55%) followed by strain (18%). The inferior members were the most affected region. Judo was the subject in which the greatest number of injuries occurred. Students stated that salient probable causes were: agressivity of colleages in practical exercises (33%) and defective sports facilities (25%). In the professors opinion, however, the two chief causes were: students’ distraction (20%) and physical inability (20%). The establishment of an Internal Commission for the Prevention of Accidents has been suggested made up of professors, under graduate students and personnel of the Physical Education Department at the State University of Maringá. Its aims are to carry out a following up of this situation, to promote the prevention of injuries and to suggest possible improvements in the premises.